Analysis of Cardiovascular Risk Factors in Patients with Coronary Heart Disease Qualified for Off-Pump Coronary Bypass - Serhii S. Sas; Serhii A. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the prevalence of cardiovascular risk factors for circulatory diseases in patients with coronary heart disease (CHD) after coronary bypass surgery (off-pump coronary artery bypass grafting).Material and methods. The study included 991 subjects (786 men, 205 women), mean age 64.3 ± 1.4 years. All the study participants underwent off-pump coronary bypass surgery.Results. Based on modern ideas about risk factors for circulatory diseases and CHD, it is impossible to ignore the influence of cardiovascular factors, both modifiable and non-modifiable. The analysis of medical and social risk factors for CHD, which include age, body weight, eating habits and smoking, showed that these medical and social factors are common among patients with CHD. It was found that the prevalence of excess body weight among men with CHD was significantly higher in patients with multivessel lesions than in those with 1-vessel lesions (p=0.05, χ2=3.69). Among women with CHD, excess body weight was significantly higher in the clinical group with multivessel lesions compared to 2-vessel lesions (p=0.002, χ2=9.06). It was also found that the prevalence of excess body weight was significantly higher in clinical groups with 1-vessel lesions among men compared to women (p=0.04, χ2=3.95). It was established that the frequency of obesity was significantly more common in women of different clinical groups compared to men: with 1-vascular lesions (p=0.04, χ2=3.95); with 2-vessel lesions (p=0.0001, χ2=24); with multivessel lesions (p=0.0001, χ2=186.57). It was established that men smoke significantly more often than women (p=0.0001, χ2=31.22). The obtained results complement the scientific data of the world epidemiological studies regarding the determination of the role of medical and social factors in the development of CHD. The article analyzes excess body weight, obesity and smoking as the leading etiological factors for CHD. It was established that the risk of developing CHD is reliably associated with excess body weight, obesity and smoking, among different clinical groups of male and female patients, both with single-vessel lesions and with multivessel lesions in CHD.Conclusions. Analysis of cardiovascular risk factors for the development of CHD, which include age, body weight, eating habits, and smoking, showed that their further study is relevant, as these are common among patients with CHD. It was established that frequency of excess body weight in patients with CHD, both in men and women, was significantly higher among individuals with multivessel lesions. The prevalence of obesity among patients with CHD presented for off-pump coronary artery bypass grafting was significantly higher among women in groups with different numbers of affected coronary vessels. As for smoking, it was established that this behaviorally associated habit is significantly more common among men with CHD. The reliable patterns of prevalence of excess body weight, obesity and smoking in patients with CHD established as a result of the study of cardiovascular factors prove that these factors have high etiological contribution to the development, course and number of affected vessels in CHD.